Formation of self-defense in the western region of Ukraine (1944-1954 years) - Резницька, Вікторія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the article describes an historical facts of the protection public order group creation in the western regions of Ukraine.